Mulheres e justiça criminal: vozes (des)consideradas e experiências vivenciadas - as usuárias da Casa-Abrigo Regional do ABC (2001-2004) - Gomes, Janete Alves (2008)
The violence against women consists of a complex theme and an existent millenarian phenomenon in all the cultures, social classes, races/ethnicities and generations that it seeks the conservation of the women's dominance-exploration and your control on the part of the men. Violence maidservant's crimes more practiced against women they are it of light deceitful bodily harm (LCD) and he/she threatens whose trial up to 1995 was foreseen by the penal code of 1940. Starting from September 26 of this same year it was promulgated the Law 9.099/95 that started to lead the procedural rite. To present research it was accomplished with women of the Regional House-shelter of ABC, that were sheltered in the period from 2001 to 2004. The object of this study refers to the women's expectations in situation of life risk due to the domestic violence about the Criminal Justice. They consisted objectives of this research: to investigate the women users' of the Regional House-shelter of ABC expectations on the paper of the justice in the resolution of your conflicts; to investigate the criminal justice through the law 9.099/95, he/she assisted to the sheltered women's needs; to verify the conciliation proposed by the Law 9.099/95 it took effect for sheltered them; to evaluate if there were impacts of the House-shelter in the women's life. The sheltered women's experiences and the interviews accomplished with these already uncovered they allowed we observe that referred her law as well as your implementation didn't answer to your needs and they after they go by audience they stayed with the unaffected risk situation and your husbands/partners they continued them threatening. In what he/she concerns the methodology this research it used the gender concepts and patriarchy because we believed that one of they separately doesn't give bill of the complexity of this reality. It was treated of bibliographical and documental research complemented with data obtained in the interviews with the former-users